12. Endothelial pump and barrier function. (September 2020) - Klyce, Stephen D.
Abstract: The mammalian cornea maintains its thickness and transparency primarily by the activity of a fluid pump located in the endothelial cell layer. The accepted concept, the "pump-leak" theory, holds that the active transport of solute from the stroma to the aqueous humor leads to a steady state osmotic pressure gradient across the endothelium that balances the imbibition pressure created by the hydrophilic proteoglycans in the stromal ground substance. The details of this process are controversial and some of the classical in vitro studies aimed to explore the fluid pump using low temperature to challenge the regulatory behavior cannot be duplicated in vivo. The activity of sensory or sympathetic innervation may play a role in this low temperature tolerance. Asymmetry in endothelial cell volume regulation could be the basis for the fluid pump. Highlights: The pump-leak theory for the corneal endothelial control of corneal hydration, although decades old, is still valid. This theory holds that the transport of solute creates an osmotic gradient to balance the stromal swelling pressure. The associated term "fluid pump" is a misnomer in that steady state fluid flow is a consequence of the solute transport. Sensory and/or sympathetic corneal innervation may play a role in the regulatory process. Asymmetry in endothelial cell volume regulation could be the basis for the fluid pump.